UJI HIPOTESIS DUA SAMPEL - Atikah Rahmah Nasution; Raphli Ardhana; Almira Amir (Pendas : Jurnal Ilmiah Pendidikan Dasar, 2025)
This study was conducted to review various journals discussing the application of two-sample hypothesis testing in the context of quantitative research in statistics courses. The review was conducted using a literature review method, namely taking references or data sources from reading materials such as journals and articles. The results of this study are to observe the application of the two-sample t-test to test the effectiveness after the application of the two-sample hypothesis test with the type of independent sample test and paired sample test. The findings also revealed that the selection of the test type is greatly influenced by the fulfillment of the assumptions of normality and uniformity of variance. Several articles emphasize the importance of sample size, the validity of the measuring instrument, and control for interfering variables to increase the reliability of the results of the hypothesis test. Overall, this review concludes that two-sample hypothesis testing is an efficient and widely used statistical analysis method, but its application must be accompanied by a deep understanding of statistical assumptions for accurate interpretation.